Desert Rituals/Campus Rituals: Tempe, Arizona - Antoine Predock (Oz, 1986)
Architecture in the Southwest may echo both the physical and human setting of its locus. In my work I attempt to merge an image of the powerful, surreal landscape of the American Southwest with an evocation of the region's cultural stratigraphy to produce an architecture that transcends both historicism and regionalism...